2004
DOI: 10.1002/ejlt.200400955
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic synthesis of medium‐chain triacylglycerols by alcoholysis and interesterification of copra oil using a crude papain lipase preparation

Abstract: We have examined the possibility of producing analogs of medium-chain triglycerides (MCT) from copra oil, i.e. a triacylglycerol mixture with a high content of medium-chain fatty acid moieties (C 6 -C 10 ). A two-step enzymatic process was used in which copra triacylglycerols were first split with papain lipase by alcoholysis with an alkyl alcohol and then subjected to interesterification with the alkyl esters recovered using papain lipase. Effects of temperature, water activity/content, substrate ratio, bioca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 27 publications
4
15
0
Order By: Relevance
“…Researchers have explored lipases from several sources for this purpose and their usage requires extensive prior optimization protocols. Caro et al (2004) used copra oil as the substrate and crude papain lipase as the enzyme for a two-step synthesis of MCT oil. First, the alcoholysis of copra oil triglycerides with butanol was initiated.…”
Section: Enzymatic Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have explored lipases from several sources for this purpose and their usage requires extensive prior optimization protocols. Caro et al (2004) used copra oil as the substrate and crude papain lipase as the enzyme for a two-step synthesis of MCT oil. First, the alcoholysis of copra oil triglycerides with butanol was initiated.…”
Section: Enzymatic Synthesismentioning
confidence: 99%
“…Caro et al. (2004) used copra oil as the substrate and crude papain lipase as the enzyme for a two‐step synthesis of MCT oil. First, the alcoholysis of copra oil triglycerides with butanol was initiated.…”
Section: Approaches For the Synthesis Of Mct Oilmentioning
confidence: 99%
“…Studies carried out on C. papaya showed that its crude latex has a very strong activity on shortchain triacylglycerol (TAG) and sn3 stereoselectivity in hydrolysis reactions of chiral TAG substrates (Villeneuve et al, 1995). These observations led to industrial use of this latex in particular applications, such as the synthesis of low-calorie triacylglycerols (Foglia and Villeneuve, 1997a) or medium-chain TAG (Caro et al, 2004). These results have prompted interest in other latex plant extracts, in particular, the unripe fruit of the babaco plant (Vasconcellea X Heilbornii cv., ex Carica pentagona Heilbornii) (Kyndt et al, 2005), a member of the papaya family native to the subtropical mountains of Ecuador, which contains a latex similar to the one in C. papaya.…”
Section: Latex Sources and Plant-based Latexmentioning
confidence: 99%
“…It is worth noting that only a few microbial lipases, such as that of Thermomyces lanuginosus (Humicola lanuginosa) (Boel and Huge-Jensen, 1998) have shown similar levels of resistance so far in a large pH range up to pH 10. Concerning lipase activity, the majority of reactions are often carried out in nearly neutral to alkaline pH (Tecelão et al, 2012;Caro et al, 2004;Lee and Foglia, 2000). For example, the CPL mediated hydrolysis in olive oil found its optimum at pH levels between 9 and 9.5 (Abdelkafi et al, 2011), while the SA in the hydrolysis of TAGs present in human diet was better at pH 6 .…”
Section: Enzymatic (Lipase) Properties Of Some Latexmentioning
confidence: 99%
“…Recently, the presence of hydrolytic enzymes such as GDSL-motif carboxylester hydrolase [6] or lipase has been demonstrated [7]. For the latter, an important characterization of its biocatalytic activities has been carried out [8][9][10][11], and some potential applications were also described in the field of racemic mixture resolution [12][13][14], oil and fat restructuration [15][16][17], and enzyme replacement therapy [18]. Regarding other molecular species naturally present in the non-watersoluble fraction of CPL, very little information exists, particularly for lipids, for which little if any characterization can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%